Práctica de enseñanza con una perspectiva intercultural, análisis de caso en segundo año en la unidad educativa del Milenio Jatun Kuraka Otavalo - Fueres Perugachi, Edgar Vicente (2016)
The following investigative work was completed at the Educative Unity of Milenio “Jatun Kuraka Otavalo” located in the community of lower San Juan, section of Otavalo, province of Imbabura, according to the theme, “Teaching practices with an intercultural perspective, second year analysis in the Educative Unity of Milenio ‘Juan Kuraka Otavalo”. Information for this work was compiled through direct observation of the intercultural practice of everyday learning and teaching with children in the classroom. Various tools were used in the collection of this information such as interviews, field diaries, and observation forms. Once the data was collected, it was then analyzed, where the most important teaching moments and practices were prioritized in order to understand the major fundamental points in the theories and arguments of our analysis. Focusing on the objectives of this investigation through direct observation, this work is important in explaining the intercultural practices in classrooms, taking into consideration curricular reforms and intercultural practice as a central concept in the national education system. With this observation, one can confirm that in the education of children in their second year at the previously mentioned institution, there is evidence of intercultural practices, although it may be of partial form due to the use of intercultural materials and elements in only a few instances of teaching and learning inside the classroom